Improving Mathematics Achievement of Special Sports Class Students Through Project-Based Learning: A Quasi-Experimental Study - Meilani Putri Pertiwi; Christina Eva Nuryani; Koryna Aviory (MATHEMA: JURNAL PENDIDIKAN MATEMATIKA, 2026)
This research aims to determine the effect of Project-Based Learning on mathematics learning achievement in Special Sports Class (SSC) students. This quasi-experimental study uses a posttest-only control design. Sampling was conducted using random sampling, with two classes selected as the experimental and control groups. The instruments used were validated learning achievement tests and observation sheets to measure the implementation of learning. Data analysis was performed using the t-test with normal and homogeneous assumptions. The results of the analysis of the implementation of learning were in the very good category with an average of 98.25%. Based on the hypothesis test, it was found that p-value = 0.000 < 0.05, so H0 was rejected. This shows that the mathematics achievement of SSC students at SMA Negeri 1 Sewon is more influenced by the project-based learning model than the cooperative model.